Leveraging Urbanization to Promote a New Growth Model While Reducing Territorial Disparities in Morocco : Urban and Regional Development Policy Note - Lall, Somik; Mahgoub, Ayah; Maria, Augustin; Touati, Anastasia; Acero, Jose Luis (Washington, DC: World Bank, 2019)
Today 60 percent of Moroccans reside in urban areas, as opposed to 35 percent in 1970. By 2050, nearly three-quarters of the country’s population will be living in cities. Along with the concentration of people, urbanization will lead to the increasing concentration of economic activities in cities, which today are estimated to account for about 75 percent of the country’s GDP and 70 percent of investments at the national level. To accompany these transformations, the Moroccan government has adopted, in recent years, ambitious programs to improve living standards in urban and rural areas. Significant improvements in living standards have been achieved through national master plans.